The madness of crowds [large type] - Penny, Louise (Penny, Louise. Three Pines mystery, 2021)
"Chief Inspector Armand Gamache is asked to provide security for a visiting Professor of Statistics at the nearby university. It sounds easy enough. That is until Gamache discovers an agenda so repulsive he begs the university to cancel the lecture. They refuse and accuse Gamache of censorship. Before long, Professor Abigail Robinson's views start seeping into conversation. Discussions become debates, debates become arguments, which turn into fights. As sides are declared, a madness takes hold. When a murder is committed it falls to Gamache and his team to investigate"--